Upaya Meningkatkan Hasil Belajar IPA Menggunakan Model Pembelajaran Problem Based Learning (PBL) Di Kelas V SDN Buket Panyang - Zubaidah; Rosina Zahara (Kilau Publishing, 2023)
The aim of this research is to determine the improvement in science learning outcomes using the Problem Based Learning (PBL) model in class V at SDN Buket Panyang. The research carried out was classroom action research (PTK). This PTK consists of 2 cycles with the research subjects being 21 class V students at SDN Buket Panyang. The data analysis technique was carried out descriptively. The research results obtained were that the student learning outcomes in the pre-cycle average score were 47.86 with student completeness 14.3%, in the first cycle the average student score was 66.43 with student completeness 61.9% , and in cycle II the average student score was 81.43 with student completeness 90.5%. Based on these results, it can be concluded that the use of the Problem Based Learning (PBL) model can improve student learning outcomes in Class V science subjects at SDN Buket Panyang.